PENEGAKAN HUKUM PIDANA TENTANG PEMILIHAN UMUM (STUDI KASUS PADA PEMILIHAN ANGGOTA DPR, DPD DAN DPRD DI SUMATERA BARAT TAHUN 2009) - Ardyan, Ardyan; Ismansyah, Ismansyah; Yoserwan, Yoserwan (STKIP Pesisir Selatan, 2024)
The criminal provisions in each law regarding General Elections (Elections) always increase, this is because there are still acts which in previous elections were not regulated as election crimes. The 2004 and 2009 Election Laws regulate procedural law and time limits for enforcing election criminal law. The Chairman of the Indonesian Election Supervisory Agency (Bawaslu), the Chief of the Indonesian Police and the Attorney General have made a Memorandum of Agreement to form an Integrated Law Enforcement Center (Sentra Gakkumdu) which contains elements from the Police, Prosecutor's Office and Election Supervisory Committee (Panwaslu) and is formed at the center, province and districts/cities which aims to effectively handle election crimes in accordance with the principles of justice, namely fast, simple and low cost as well as free, honest and impartial. The enforcement of election criminal law in the 2009 elections should have been more effective, but it turns out that based on Bawaslu's report the enforcement of election criminal law was very ineffective. This can be seen from the 2629 cases of election criminal violations, only 215 of which were decided in court. Referring to this problem, using a sociological juridical (empirical) legal research method, namely research carried out by analyzing data sources and then conducting interviews to reveal what problems occurred, what the coordination pattern actually was carried out by the Panwaslu with the Gakkumdu Center, how the Panwaslu and The Gakkumdu Center follows up on reports/findings of violations of election crimes, to determine whether many cases forwarded by the Panwaslu to the Gakkumdu Center are declared not to be election crimes, or there is not enough evidence, or the time for resolving election crimes will exceed the time limit, as well as looking for any factors which is an obstacle for both Panwaslu and the Gakkumdu Center in enforcing the law for election crime violations. From the research results, it turns out that coordination between the Panwaslu and the Gakkumdu Center went well, but enforcement of the criminal law for the election of members of the DPR, DPD and DPRD in 2009 failed, this was because reports submitted to the Panwaslu were reviewed and then submitted to the Gakkumdu Center to be reviewed again before being forwarded. to investigators. In the end, the Gakkumdu Center is no longer a forum for speeding up the resolution of handling election crimes, instead it acts as a filter for cases that will be passed on to the trial stage. Apart from that, there is a problem of differences in perception between who has the authority to declare suspected criminal acts, whether the Panwaslu or the Police, and then there is a shifting of duties between each other. for collecting evidence between Investigators and Panwaslu, and it cannot be denied that the quality of Panwaslu's human resources is very limited, most recently due to time restrictions for enforcing election criminal law as regulated in the law on elections. Therefore, it would be better if the law on elections strengthens the position of the Gakkumdu Center as the central institution for reporting and enforcing election criminal law, no longer the Panwaslu.